Development and Bio-Predictive Evaluation of Biopharmaceutical Properties of Sustained-Release Tablets with a Novel GPR40 Agonist for a First-in-Human Clinical Trial - Ewelina Juszczyk; Kamil Kisło; Paweł Żero; Ewa Tratkiewicz; Maciej Wieczorek; Jadwiga Paszkowska; Grzegorz Banach; Marcela Wiater; Dagmara Hoc; Grzegorz Garbacz; Jaroslaw Sczodrok; Dorota Danielak (MDPI AG, 2021)
Sustained-release (SR) formulations may appear advantageous in first-in-human (FIH) study of innovative medicines. The newly developed SR matrix tablets require prolonged maintenance of API concentration in plasma and should be reliably assessed for the risk of uncontrolled release of the drug. In the present study, we describe the development of a robust SR matrix tablet with a novel G-protein-coupled receptor 40 (GPR40) agonist for first-in-human studies and introduce a general workflow for the successful development of SR formulations for innovative APIs. The hydrophilic matrix tablets containing the labeled API dose of 5, 30, or 120 mg were evaluated with several methods: standard USP II dissolution, bio-predictive dissolution tests, and the texture and matrix formation analysis. The standard dissolution tests allowed preselection of the prototypes with the targeted dissolution rate, while the subsequent studies in physiologically relevant conditions revealed unwanted and potentially harmful effects, such as dose dumping under an increased mechanical agitation. The developed formulations were exceptionally robust toward the mechanical and physicochemical conditions of the bio-predictive tests and assured a comparable drug delivery rate regardless of the prandial state and dose labeled. In conclusion, the introduced development strategy, when implemented into the development cycle of SR formulations with innovative APIs, may allow not only to reduce the risk of formulation-related failure of phase I clinical trial but also effectively and timely provide safe and reliable medicines for patients in the trial and their further therapy.